2006
DOI: 10.1016/j.ygeno.2005.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and supragenomic structure of the nucleotide-like G-protein-coupled receptor GPR34

Abstract: Directed cloning approaches and large-scale sequencing of several vertebrate genomes unveiled many new members of the G-protein-coupled receptor (GPCR) superfamily, among them GPR34. Initial studies showed that GPR34 is an evolutionarily old GPCR structurally related to a group of ADP-like receptors. To gain insight into the genomic organization, regulation of expression, and supragenomic diversification of GPR34 several vertebrate species were analyzed. In contrast to the obviously intronless coding region GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Increased DTH Reaction in GPR34-deficient Mice-Because GPR34 is highly expressed in immune cells (10,16,40), we challenged the immune system in a DTH test to screen for differences between WT and KO mice. The DTH test investigates the reaction of the organism toward an antigen after prior immunization.…”
Section: Gpr34-deficient Mice Show No Obvious Phenotype Under Specifimentioning
confidence: 99%
See 2 more Smart Citations
“…Increased DTH Reaction in GPR34-deficient Mice-Because GPR34 is highly expressed in immune cells (10,16,40), we challenged the immune system in a DTH test to screen for differences between WT and KO mice. The DTH test investigates the reaction of the organism toward an antigen after prior immunization.…”
Section: Gpr34-deficient Mice Show No Obvious Phenotype Under Specifimentioning
confidence: 99%
“…More detailed analyses showed GPR34 expression in the myeloid progenitor cell line HL-60 in K562 cells, and WEHI-3B cells, the macrophage cell line RAW 264.1 (10), and in the murine mast cell line P815. These findings suggest a granulocytic/monocytic expression pattern that is consistent with the ubiquitous expression pattern seen in tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…GPR34 is highly expressed in immune cells (macrophages and microglia) (6,9) and immune system-derived cell lines (HL-60, K562, WEHI-3B, RAW 264.7, P815) (10). Immune systemchallenging conditions on mice showed that GPR34 deficiency results in an improper immune response, with higher susceptibility to systemic infections (6).…”
mentioning
confidence: 99%
“…11,12 The receptor mRNA is ubiquitously expressed in all human tissues, particularly in placenta, brain and spleen. 13 Recent studies suggest that GPR34, found to be abundantly expressed in mast cells, is the functional mast cell receptor for lysophosphatidyl-L-serine (lysoPS).…”
mentioning
confidence: 99%